La psichiatria perinatale . Introduzione - Panzera, Ferdinando (Il sogno della farfalla, 2019)
This article introduces a number of papers dealing with the complex topic of psychiatric pathologies affecting women during the perinatal period. The research conducted by Massimo Fagioli on human birth has been the main thread followed to study the psychopathology of these diseases: starting from what occurs in the newborn’s mind at birth, followed by the moment of silence and suspension immediately after delivery (this moment was defined by Fagioli “twenty seconds”) and finally looking at the mother’s reaction to the relationship with the newborn. The connection between the historical female oppression and negation and perinatal pathologies has been particularly highlighted. Often psychopathological alterations related to childbirth occur as a consequence of a difficulty in comprehending and accepting the realization of a human being’s birth. Therefore, understanding these dynamics might provide a different perspective in order to deal with these pathologies and at the same time may prevent a potential psychic suffering in newborns.